Tracing Heavy Metal Dynamics in Mangrove Sediments: A Study from Ujung Kulon National Park - Dienda Shintianata; Ali Arman Lubis; Untung Sugiharto; Faza Putri Andini; Sonia Saraswati Meiliastri; Md Suhaimi Elias (Ilmu Kelautan)
The dynamics of heavy metal concentrations in the sediments of mangroves are crucial for understanding the health and sustainability of these ecosystems. This study, conducted in a conservation area of Ujung Kulon National Park (UKNP) in Indonesia, investigated the distribution of heavy metals in mangrove sediments, which are vital in trapping these potentially harmful substances due to their absorption, sedimentation, and bioaccumulation capabilities. By analyzing sediment cores from different intertidal zones (interior, fringe, and mudflat) through Inductively Coupled Plasma - Optical Emission Spectrometry (ICP-OES), this study examined concentrations and distribution patterns of six heavy metals: manganese (Mn), copper (Cu), zinc (Zn), cobalt (Co), chromium (Cr), and Iron (Fe). The results indicated that the average concentration of heavy metals followed a decreasing order of Fe> Mn > Zn > Cu > Cr> Co across all locations. All of the heavy metals in the interior and fringe increased gradually from the year 1900 to the present; on the contrary, the mudflat decreased over the same period. Enrichment Factor (EF) and Geo Accumulation Index (Igeo) were used to evaluate heavy metal pollution levels comprehensively. The study revealed temporal trends in heavy metal concentrations, highlighting the need for further research to mitigate these contaminant's effects on mangrove ecosystems. By integrating the EF, the Igeo index, and quality standards, the research demonstrates that UKNP is likely pristine. Furthermore, this work emphasizes the need to utilize dated environmental archives to reconstruct historical patterns in trace metal pollution in locations where long-term environmental studies remain particularly limited